Clamor Schürmann's Barngarla grammar : a commentary on the first section of A vocabulary of the Parnkalla language - Clendon, Mark (The University of Adelaide, University of Adelaide Press, 2015)
This book should be seen as one of a number of starting points for language-reclamation endeavours in Barngarla, designed primarily for educators and other people who may wish to re-present its interpretations in ways more accessible to non-linguists, and more suited to pedagogical practice.